[Druk ulotny. Incipit] Danzig d.4t. Januar 1879. ([Miejsce nieznane] : [wydawca nieznany], 1879)
Karnecik na bal z listą tańców.
Keywords: Bale -- Polska -- 19 w. -- druki ulotne; Gdańsk (Polska) -- 1870-1914 -- druki ulotne; Druki ulotne -- 19 w